LINKAGE OF ARTS AND HUMANITIES: AN ENVIRONMENTAL APPRAISAL OF IRAN - Sheykhi, Mohammad Taghi (International Journal of Research -GRANTHAALAYAH, 2018)
Graphic signs and symbols could largely affect the changing environment by the youth and within the youth in the present societies with special reference to the developing Iran. Transfer of young cohorts to cities in search of better income and higher quality of life has extensively impacted the urban environment through more emissions, more transportation, more consumption and the like. Increasing understanding of ecological system, promoting efforts to prevent damage to the environment, declaring national policies to the encourage productive and enjoyable harmony between man and environment and improving understanding among the families and the youth in association with the natural and built- environment, all could be supervised and controlled by graphic informatics. Graphics as a theoretical paradigm explores the relationship between human culture and the natural environment. In the present survey, some 419 youth of the both genders were interviewed through designed questionnaires.